"I Don't Want You in My Country": Migrants Navigating Borderland Violences between Colombia and Chile. Issue 5 (14th June 2022) - Ryburn, Megan
Abstract : Through the lens of "navigating borderlands, " this article brings together the anthropology-derived concept of social navigation (Vigh 2006 ) with a feminist geography approach to borderlands, enriching both. It is based on ethnographic research with Colombian and Venezuelan migrants along the 4, 500-km migration route from the Valle del Cauca, Colombia, to Antofagasta, Chile, and additionally informed by further multisited ethnography in Antofagasta and the Valle del Cauca. The borderlands perspective bridges gaps between migration, border, and mobility studies by combining feminist scholarship on transnational social spaces and borders and violence with a reflexive migration trajectories methodology. It considers how the shifting space of the often violent borderland is constructed through interactions between diverse actors. Paying greater attention to the construction of space enhances the analytical potential of social navigation. In turn, analyzing actors' negotiations of the borderland in terms of navigation illuminates how they move in and through unpredictable spaces. Specifically, this article considers how actors including border officers, transport providers, scammers, and nongovernmental organization workers "police, " "move, " and "reroute" in the borderland. It also reveals how migrants navigate interactions with these varied actors to aguantar (endure/cope/hold on); although not resistance per se, aguantar may sometimes be a form of defiance.